Introduction to dislocations, fifth edition - Cambridge, Derek Hull Emeritus Goldsmith's Professor University of.; Bacon, D. J. ([S.l.] : Butterworth-Heinemann, 2011)
Dislocations are defects in the crystal structure of important engineering materials, such as metals, ceramics and semi-conductors, that strongly influence the properties of these materials. Research on dislocations was intense when the first edition of this classic work was published in the 1960s. By incorporating later developments in subsequent editions whilst retaining a concise, accessible style, Introduction to Dislocations has become established as a key resource for students, graduates and researchers. No other book on the topic is as credible and, with this new edition, as up-to-date. Introduction to Dislocations is widely recognized to provide the essential knowledge base required for further study, research and technological application in the field. This update brings the book's coverage, references and context in line with the latest developments to ensure it remains a core reference for all those studying and working in the field today. Long-established academic reference by an expert author team, highly regarded for their contributions to the field. Uses minimal mathematics to present theory and applications in a detailed yet easy-to-read manner, making this an understandable introduction to a complex topic. Unlike the main competition, this new edition includes recent developments in the subject and up-to-date references to further reading and research sources.
Keywords: Dislocations in crystals; Dislocations in crystals; Dislocations in crystals; Dislocations in crystals